(untitled) (ENTHYMEMA, 2025)
In recent decades, the family novel has taken on a central role in hyper-contemporary Italian fiction, evolving through a continuous dialogue with other genres and narrative modes. This study aims to examine La più amata (2017) by Teresa Ciabatti and Niente di vero (2022) by Veronica Raimo, two novels that exemplify this transformation, focusing on their intersection with autofiction and the coming-of-age novel. Adopting a comparative perspective, the article explores strategies for representing family identity, the tension between reality and fiction, the fragmentation of narration, and the subversion of the linear trajectory of character development. The hyper-contemporary Italian family novel thus emerges not only as a space for critical reflection on identity and genealogical bonds but also as a terrain for literary experimentation, where the interplay of genres and the fluidity of their boundaries are investigated.